Generation of virtual asphalt mixture porosity for computational modelling - Chiarelli, Andrea; Dawson, Andrew; Garcia, Alvaro (Elsevier, 2015)
A new algorithm is proposed for the computational generation of realistic asphalt mixture porosity for computational simulations. The algorithm starts by generating in a 2D domain a number of randomly positioned circular or elliptical elements that are meant to represent virtual asphalt aggregate particles. These elements are then grown by mimicking the biological mechanism called contact inhibition until a target air void content (AVC), chosen by the user, is met. In addition, multiple 2D domains can be converted to 3D and combined to generate a multi-layered realistic representation of the porosity present in asphalt mixtures. In this paper, the working mechanism of the algorithm is described and its efficiency is assessed. Moreover, the validity of the results is discussed, and virtual domains, in both 2 and 3 dimensions, are compared with real CT scans in order to show the efficacy of this approach. It was found that the virtual representations of the asphalt mixture porosity show realistic characteristics in terms of air void content and that the air void size distribution is consistent with that of real specimens.